"You Just can't Trust them": Exploring the Memorable Messages Costa Rican Natives Recall about Race. Issue 4 (4th July 2018) - Nuru, Audra K.; Coleman, Marcus J.; Saxton Coleman, Loren
Abstract: This study uses memorable messages as a framework for understanding how Costa Rican youths are socialized about race. Through semi-structured interviews, twenty-three participants identified a total of 107 memorable messages, of which three themes emerged: (a) denial of racism, (b) preparation for bias, and (c) promotion of mistrust. Findings reveal that participants use memorable messages to make sense of racial hierarchies in Costa Rica while also highlighting patterns of racial socialization that are consistent across global contexts. In addition to examining the individual-structure dialectic, this research addresses post-racial and color-blind narratives that permeate discourses in Latin American nations.